PENGAWASAN PEMERINTAH PADA USAHA DEPOT AIR MINUM DI KECAMATAN MAKASSAR KOTA MAKASSAR - BAHARUDDIN, HENDRAWAN (Universitas Sulawesi Barat, 2022)
The purpose of this study was to study government oversight of drinking water depot businesses in Makassar District, Makassar City. The type of research used in this study is a type of qualitative descriptive study with a type of case study. Data collection techniques used by researchers were interviews with eight informants, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. The validity of the data is used triangulation namely time triangulation, source triangulation, and technique triangulation. The results of this study indicate that government oversight of drinking water depot businesses in Makassar City Makassar District is still very far from what is expected to be seen from preventive and repressive supervision by three government agencies, including the Investment Office, the Industry and Trade Service and the Makassar City Health Service because there are still many public water depot businesses in Makassar City Makassar District that have not pocketed administrative requirements.